포토보이스 조사방법을 활용한 대학생이 지각한 정신건강의 의미와 영향요인 탐색 - 이소원(Sowon Lee); 김경숙(Kyungsook Kim); 김보영(Boyoung Kim) (保健敎育健康增進學會誌, 2017)
Objectives: The purpose of this study was to explore how university students perceive the mental health, what are the factors affecting the mental health in their lives. Methods: The participants of this study were eight university students who haven't participated in a class of mental health, residing in G city. This study collected the data between May 9 and June 13, 2016, and adopted a photovoice methodology of participatory action research. Results: The mental health perceived by the participants was expressed as new things re-experiencing in a familiar daily life of themselves, and things seem the same but different from others. Through discussion, the participants found that affecting factors of the mental health they negatively perceived could work on others as positive factors. Also, the participants were in search of a strategy to individually protect the mental health barriers in ways of that could contribute to mental health of the community such as conformity to social regulations. Conclusions: Based on these results, this study was meaningful in that various views were derived to prepare strategies and policy alternatives to promote university students' mental health.